1987
DOI: 10.1136/thx.42.11.889
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae pneumonia in Melanesian adults: report of 15 cases.

Abstract: In a prospective study of 170 adult patients with acute pneumonia, Haemophilus influenzae was found to be the aetiological agent in 15 cases (8-8%). The diagnosis in all cases was based on positive cultures of blood or percutaneous lung aspirate, or both. Chronic lung disease was significantly more common in patients with H influenzae pneumonia than in patients with pneumonia due to other organisms but age, sex, and smoking history did not differ significantly. Lobar consolidation was the most common radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…at species-level. The specific qRT-PCR confirmed 12 of 14 RPM-positive results for H. influenzae which might be the causative agents of CAP (Barnes et al, 1987 ) and was of particular importance for respiratory infections in children (Nascimento-Carvalho, 2001 ). Haemophilus parainfluenzae and Haemophilus haemolyticus , the other two types of Haemophilus spp., were commonly considered as commensals colonizing the upper respiratory tract asymptomatically (Mukundan et al, 2007 ; Murphy et al, 2007 ).…”
Section: Discussionmentioning
confidence: 57%
“…at species-level. The specific qRT-PCR confirmed 12 of 14 RPM-positive results for H. influenzae which might be the causative agents of CAP (Barnes et al, 1987 ) and was of particular importance for respiratory infections in children (Nascimento-Carvalho, 2001 ). Haemophilus parainfluenzae and Haemophilus haemolyticus , the other two types of Haemophilus spp., were commonly considered as commensals colonizing the upper respiratory tract asymptomatically (Mukundan et al, 2007 ; Murphy et al, 2007 ).…”
Section: Discussionmentioning
confidence: 57%
“…Over the last several decades, cases of HINP have been described in patients with COPD, alcoholism, immunological deficiencies, sarcoidosis, and other conditions [6,8,23]. BARNES et al [4] confirmed the association of H. influenzae community acquired pneumonia with chronic bronchitis, but did not establish its association with alcoholism or other conditions. This type of pneumonia was produced by microaspiration of oropharyngeal contents, and this mechanism has been confirmed in an experimental model [24].…”
Section: Discussionmentioning
confidence: 99%
“…Haemophilus influenzae (HI) frequently colonizes the trachea and major bronchi of smokers and patients with chronic obstructive pulmonary disease (COPD) [1]. H. influenzae infection is a common aetiology of exacerbations in COPD [2], and causes community-acquired pneumonia (CAP) in children and adults with chronic diseases, such as COPD or alcoholism [3,4]. Nosocomial outbreaks of H. influenzae infection have recently been reported both in children and adults with chronic underlying disease [5].…”
mentioning
confidence: 99%
“…Another study conducted in Papua New Guinea prospectively examined 170 adult patients with acute CAP. Of these, H. influenzae was identified as the sole pathogen in 15 (9%) patients: 7 Hib, 4 serotype a (Hia), 1 Hic, and 3 NTHi [118]. Chronic lung disease was more common in patients with H. influenzae pneumonia than CAP due to other organisms.…”
Section: H Influenzae As a Cause Of Community-acquired Pneumonia mentioning
confidence: 99%